Observations Made with Glucocorticoids in the Treatment of Acute and Chronic Liver Diseases - Oliveros Loyola, José Humberto (1971)
Fifty patients receiving corticosteroid medication were studied for each different type of liver disease suffer and those who received such medication and other disease processes in which the underlying liver pathology observed or consecutive to that administration. The author concludes that corticosteroids may be used in tables or prolonged torpid evolution, in acute cases, the des progressive offset, or to prevent the entry point of the chronic cases. The dose reduction should be tapered in shape to avoid the rebound phenomenon.